2019
DOI: 10.1186/s12958-019-0477-8
|View full text |Cite
|
Sign up to set email alerts
|

Serum Antimüllerian hormone does not predict elevated progesterone levels among women who undergo controlled ovarian hyperstimulation for in vitro fertilization

Abstract: Serum Antimüllerian hormone (AMH) has been shown to predict various in vitro fertilization (IVF) outcomes. AMH and progesterone (P) are products of granulosa cells of the ovary. Since overall granulosa cell number directly correlates with oocyte number and AMH production, the aim of this study is to evaluate whether or not serum AMH is associated with elevated P during controlled ovarian hyperstimulation (COH) for IVF. For this retrospective study, data were abstracted from charts of first IVF cycles of women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
(24 reference statements)
1
2
0
Order By: Relevance
“…However, AMH has not been shown to predict P4 rise on the day of oocyte aspiration. Our finding is consistent with a recent study by Kavoussi et al 25 , who also did not find a predictive value of AMH in P4 rise. Studies have shown that AMH can predict the response to ovarian stimulation as well as the number of achieved oocytes and embryos; however, its correlation with P4 rise has not been extensively studied 25 .…”
Section: Discussionsupporting
confidence: 93%
“…However, AMH has not been shown to predict P4 rise on the day of oocyte aspiration. Our finding is consistent with a recent study by Kavoussi et al 25 , who also did not find a predictive value of AMH in P4 rise. Studies have shown that AMH can predict the response to ovarian stimulation as well as the number of achieved oocytes and embryos; however, its correlation with P4 rise has not been extensively studied 25 .…”
Section: Discussionsupporting
confidence: 93%
“…The endocrine and metabolic status of PCOS patients are relatively abnormal, which leads to important causes of abnormal uterine bleeding, infertility, and other adverse conditions, so the treatment needs of women in gestational age are often high [ 22 ]. This study aimed to investigate the relationship between the levels of endocrine and metabolic indicators and ultrasound parameters in PCOS patients.…”
Section: Discussionmentioning
confidence: 99%
“…The women from 30 to 44 years old are at high-risk of ovarian aging, and they are the main population receiving ART [5]. The clinical treatment of these patients generally adopts an "empirical" strategy, in which the choice of COH protocol is based on the patient's age, BMI, ovarian reserve, and clinical experience [23]. Before the implementation of ART, clinicians can predict the patient's ovarian response according to age-related ovarian reserve and provide patients with pre-treatment consultation.…”
Section: Discussionmentioning
confidence: 99%